Kewenangan Pelelangan Kayu Hasil Illegal Loging - Zulham Adamy; Eko Nuriyatman (Jurnal Selat, 2022)
The existence of exploitation of forest resources that are dangerous for the survival of the forest is illegal logging activities carried out without going through a selection or selective logging process and permission from the government. So related to this, this scientific article discusses the "Authority of Illegal Logging Timber Auctions," using normative juridical research methods. The normative juridical research approach is a legal research with a literature approach that is carried out by conducting research on library materials or mere secondary data. As for what is studied in this scientific article is about the mechanism of auctioning confiscated wood from illegal logging outside the conservation forest of Jambi Province. So based on this, it is obtained data that related to the auction of confiscated wood from illegal logging outside the conservation forest of Jambi Province, those who have authority in cases of confiscated wood are the forestry service and investigators/public prosecutors. However, there are also contradictions in the rule of law related to the auction of illegal logging results, namely between Article 23 number (1) of the Minister of Finance Regulation Number 213/PMK.06/2020 and Article 4 Number 2 of the Minister of Forestry Regulation Number P. 47/Menhut-II/2009 regarding the Amendment to Regulation of the Minister of Forestry Number P.48/Menhut/2006.